White-Collar Crime: The Privileging of Serious Financial Fraud in New Zealand. (August 2020) - Marriott, Lisa
Bagaric and Alexander (2014 ) argue for fundamental reform of the sentencing process for white-collar offenders in Australia and other jurisdictions. This study has two objectives. First, it challenges Bagaric and Alexander's proposals. Second, using data from cases prosecuted by the New Zealand Serious Fraud Office, it instead proposes that white-collar offenders should not receive more lenient treatment in the justice system due to the privileged position from which the offending commences. This article suggests that an absence of restitution should be considered an aggravating factor, rather than the presence of restitution viewed as a mitigating factor; as an offender's good character is often an enabler of the offending, this should not be considered as a mitigating factor and as extra-curial punishments, such as reputation damage or loss of future employment opportunities, are short-term for white-collar offenders, there is little justification for reduced sentences and extra-curial punishments can be viewed as a natural corollary of the offending.